Genome‐wide Characterization and Expression Analysis of Sugar Transporter Family Genes in Woodland Strawberry. Issue 3 (1st November 2018) - Jiu, Songtao; Haider, Muhammad Salman; Kurjogi, Mahantesh M.; Zhang, Kekun; Zhu, Xudong; Fang, Jinggui
Abstract : In higher plants, sugars are nutrients and important signal molecules. Sugar transporters (STs) facilitate sugar transport across membranes and are associated with loading and unloading of the conducting complex. Strawberry ( Fragaria ×ananassa Duchesne ex Rozier) is one of the most economically important and widely cultivated fruit crop and a model plant among fleshy fruits worldwide. In this study, 66 woodland strawberry ( F. vesca L.) ST (FvST) genes were identified and further classified into eight distinct subfamilies in the woodland strawberry genome based on the phylogenetic analysis. In the promoter sequences of FvST gene families, a search for cis ‐regulatory elements suggested that some of them might probably be regulated by plant hormones (e.g., salicylic acid, abscisic acid, and auxin), abiotic (e.g., drought, excessive cold, and light), and biotic stress factors. Exon–intron analysis showed that each subfamily manifested closely associated gene architectural features based on similar number or length of exons. Moreover, to comprehend the potential evolution mechanism of FvST gene family, the analysis of genome duplication events was performed. The segmental and tandem duplication analysis elucidated that some of ST genes arose through whole‐genome duplication (WGD) or segmental duplication, accompanied by tandem duplications. The expression analysis of 24 FvST genes in vegetative and during fruit development has shown that the expression of several ST genes was tissue and developmental stage specific. Generally, our findings are important in understanding of the allocation of photo assimilates from source to sink cell and provide insights into the genomic organization and expression profiling of FvST gene families in woodland strawberry.